Spatiotemporal variation of forest cover and its relation to air quality in urban Andean socio-ecological systems - Bonilla-Bedoya, Santiago (2021)
Confronting the dynamics of global urbanization is one of the challenges of sustainability in the 21st century. Latin America is expected to be one of the regions with the highest urban growth; however, research related to variations in urban land coverage and air quality is relatively new, despite its importance for urban planning and citizens well-being. This study determines the relationship between the spatial variability of some atmospheric pollutants and changes in land cover in a Andean mountain cities of Latin American. We quantified the changes and transitions of land cover using SPOT optical images and generating an object-based classification. In addition, we identified variations in the mean concentrations of some atmospheric pollutants; and, finally, using various linear regression models, we explained the relationship between the spatiotemporal variation of atmospheric pollutants with the spatiotemporal variations of the land cover and some meteorological and topographical factors. Changes in land cover indicated an increase of impervious cover and a loss of urban non-forest vegetation. However, there was also an increase in forest fragments and urban woodland to the detriment of green areas and shrubbery. On the other hand, the concentrations of the air pollutants CO, O3, and PM2.5 showed significant variations between periods, reducing their concentrations in the air. Finally, land cover such as forests and urban trees, as well as meteorological and topographical factors were associated with and explained (r2 > 0.6) the spatiotemporal variation of air pollutants. Urban green infrastructure management in developing regions should consider a multidisciplinary approach to achieve an equitable and minimum distribution of local green infrastructure; by promoting conditions that allow the conversion of land use and coverage, in order to maximize the benefits and the ecosystemic forest services that a city demands